Neurofilament light plasma concentration positively associates with age and negatively associates with weight and height in the dog. (23rd January 2021) - Perino, Jackie; Patterson, Margaret; Momen, Mehdi; Borisova, Mina; Heslegrave, Amanda; Zetterberg, Henrik; Gruel, Jordan; Binversie, Emily; Baker, Lauren; Svaren, John; Sample, Susannah J.
Highlights: Plasma neurofilament light chain can accurately be measured in the dog. Plasma neurofilament light chain concentration increases with age in the dog model. Plasma neurofilament light chain concentration inversely relates to weight in dogs. Plasma neurofilament light chain concentration is not associated with BMI in dogs. Abstract: Plasma neurofilament light chain (pNfL) concentration is a biomarker for neuroaxonal injury and degeneration and can be used to monitor response to treatment. Spontaneous canine neurodegenerative diseases are a valuable comparative resource for understanding similar human conditions and as large animal treatment models. The features of pNfL concentration in healthy dogs is not well established. We present data reporting basic pNfL concentration trends in the Labrador Retriever breed. Fifty-five Labrador Retrievers were enrolled. pNfL concentration was measured and correlated to age, sex, neuter status, height, weight, body mass index, and coat color. We found increased pNfL with age ( P  < 0.0001), shorter stature ( P  = 0.009) and decreased body weight ( P  < 0.001). These are similar to findings reported in humans. pNfL concentration did not correlate with sex, BMI or coat color. This data further supports findings that pNfL increase with age in a canine population but highlights a need to consider weight and height when determining normal pNfL concentration in canine populations.